PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE ROTATING TRIO EXCHANGE (RTE) DISERTAI MEDIA QUESTION BOX UNTUK MENCAPAI KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN IKATAN KIMIA DI KELAS X SMA NEGERI 1 BANDAR SEIKIJANG, PELALAWAN - Wulandari, Vivin Wulandari; ', Miharty; ', Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Research on the application of strategy active learning type Rotating Trio Exchange (RTE) be accompanied by media Question Box has been done to achieve student’s mastery learning on the subject of chemical bonds in class X SMAN 1 Bandar Seikijang, Pelalawan. Form of research is pra-experiment research with one-shotstudy case design. Data retrieval time from the date of 22 October to 26 Novenber 2014. The sample was selected from the three existing classes, namely class X MIA.1. Data analysis technique used is to calculate presentation of classical mastery learning. Based on the final results of data processing using acquired mastery learning classical is 90,91%, it’s means that the application of strategy active learning type Rotating Trio Exchange (RTE) be accompanied by media Question Box can achieve student’s mastery learning on the subject of chemical bonds in class X MIA.1 SMAN 1 Bandar Seikijang, Pelalawan. Keywords: Rotating Trio Exchange (RTE), Question Box, Mastery Learning, chemical bonds.